Peningkatan Pengetahuan Ibu Hamil Tentang Manfaat Sayuran Hijau Sebagai Upaya Mencegah Anemia Kehamilan di Puskesmas Gandus Palembang - Rini Anggeriani; Sagita Darma Sari; Wika Sepiwiryanti (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Anemia in pregnant women is still a global problem today. The World Health Organization (WHO) reported that in 2019 the incidence of anemia in pregnant women was 37%. The biggest cause of anemia in pregnant women is iron deficiency. Apart from Blood Increasing Tablets, pregnant women need to consume foods that contain Fe, namely green vegetables. The aim of the activity is to increase pregnant women's knowledge about the benefits of green vegetables in preventing anemia. Method: counseling uses a question and answer lecture method and educational videos containing the correct and appropriate way to process green vegetables. Knowledge assessment is by interview (questionnaire). Results: The average pretest score was 67.4 and the average posttest score was 81.1. These results indicate an increase in knowledge of pregnant women after being given education using lecture and video methods about the benefits of green vegetables and pregnancy anemia. It is hoped that all relevant parties will develop and improve education programs in an effort to prevent anemia in pregnant women.